Photodegradation of organic pollutants using heterojunctions: A review. Issue 2 (April 2020) - Parul,; Kaur, Kamalpreet; Badru, Rahul; Singh, Prit Pal; Kaushal, Sandeep
Abstract: Semiconductor assisted photocatalysis has attracted a pronounced attention owing to its vital role in environmental remediation. Effective light absorption, particularly in the visible region, and charge separation are the two most important factors affecting a photocatalytic system which is generally hard to be achieved by the bare photocatalysts. The blending of various semiconductor materials for the fabrication of heterojunction enhances the photocatalytic activity and stability by decreasing the rate of combination of electron-hole pairs. This review succinctly outlines the recent progress in the synthesis methods and the photocatalytic performances of semiconductor-semiconductor heterojunctions and semiconductor-carbon heterojunctions for degradation of pollutants like dyes, antibiotics, insecticides, herbicides, pesticides, and water splitting. The review ends with a summary and some future perspectives on this fast-emerging area of research.